Pengaruh Latihan Gerak Sendi Aktif dengan Kemampuan Mobilitas Fisik pada Pasien Stroke Non Hemoragik di RSUD Deli Serdang - Samuel Ginting; Chaidir Saputra; Chairani Chairani (Elisabeth Health Jurnal, 2021)
Background: Stroke is a neurological disease that ranks third as the cause of death in Indonesia after cancer and heart disease. Stroke in Indonesia is increasing due to changes in modernization lifestyle. The general purpose of this study was to determine the relationship between active joint motion exercises and physical mobility abilities in non-haemorrhagic stroke patients at the Deli Serdang Lubuk Pakam General Hospital.Methods: This type of research is descriptive analytic using a one group pre and post test design approach with a quasi-experimental design. The research location is RSUD Deli Serdang Lubuk Pakam, carried out in early February 2012. The research population was 28 people and a sample of 9 people with the sampling technique using the accidental sampling method. Data were analyzed using t test (paired sample T-test).Results: The results showed that the patient's mobility ability before being treated (pretest) with a value of 0 is 8 people (88.9%), and a value of 1 is 1 person (11.1%). The patient's mobility ability after being treated (posttest) with a value of 0 is 4 people (44.4%), and a value of 1 is 5 people (55.6%). There was an increase in the ability of physical mobility by 1.8. Active joint motion exercises affect the mobility ability of non-haemorrhagic stroke patients at Deli Serdang Hospital, Lubuk Pakam in 2012. With p value = 0.001 (α = 0.05).Conclusion: 3. There is a relationship between active joint motion exercises and mobility abilities in non-hemorrhagic stroke patients at the Deli Serdang Regional General Hospital Lubuk Pakam in 2012 with p value = 0.001 (α = 0.05).